The common: reflections on an equivocal concept - Alvaro, Daniel (2022)
This article aims to reflect on the definitions and theories of the “common” that nourish the contemporary debates around that concept. With that goal, we will interrogate the works of Christian Laval and Pierre Dardot, Michael Hardt, Antonio Negri, Jean-Luc Nancy and Roberto Esposito. The analysis of these discourses will make evident that what nowadays is understood by common, both from a philosophical and from a practical-political viewpoint, assumes different and usually confronted meanings. The article looks into the diverse meanings and uses of the concept in order to demonstrate that this semantic ambivalence is a decisive factor to understand the scope and limitations of the problem of the common in today’s world.